Constructing and providing content validity evidence through the Aiken's V index based on the experts' judgments of the instrument to measure mathematical problem-solving skills - Nia Kania; Yaya S. Kusumah; Jarnawi Afgani Dahlan; Elah Nurlaelah; Ferit Gí¼rbí¼z; Ebenezer Bonyah (REID (Research and Evaluation in Education), 2024)
Test content-based proof of validity is a type of evidence that supports the validity of a measuring instrument. This research aims to develop a mathematical problem-solving assessment instrument utilizing five experts. This study is classified as developmental research and follows a research design that includes two separate stages: the preliminary design stage and the prototype stage. However, its application is restricted to Prototype 1 and Prototype 2, specifically for expert evaluation. This instrument was designed explicitly for grade VIII students studying mathematics, covering all the topics from the odd semesters. The analysis progressed through three distinct stages "” curriculum analysis, content analysis, and context analysis "” each contributing to a comprehensive understanding of instructional resources. The study sought to narrow the gap between theoretical knowledge and practical application in mathematics education by incorporating real-world context. Surveys have revealed difficulties in answering mathematical problems, highlighting the need to address gaps in learning to improve competency. The careful and thorough construction of test instruments, considering factors such as validity, established the foundation for creating accurate assessment tools. The content validity assessment by the expert panel, with scores ranging from 0.817 to 0.884 based on the V-Aiken category, confirms that the instrument is vital in assessing students' mathematical problem -solving skills, and the implementation of this study yielded many valuable insights for educators and academics. This study helps improve mathematics education resources and evaluations to promote mathematical thinking.